PENGALAMAN MANAGEMENT IMPLEMENTASI TERAPI KOMPLEMENTER DI LAYANAN PRAKTIK BIDAN BERSAMA - ANGGRAINI, MARCELIS STIA (Universitas Aisyah Pringsewu, 2023)
Background: The positive public response as well as the high enthusiasm of pregnant women for complementary therapy makes complementary therapy an alternative choice to avoid the side effects of using chemical drugs which can have a negative impact on the womb, but until now there has been no government policy that regulates complementary therapy specifically for obstetrics. Kepahiang district was chosen as the research site because Kepahiang is the only district to have introduced innovations that require midwifery services to be delivered in a collaborative way.To examine the implementation of management experience on the complementary therapies’ implementation in joint midwife practice services (PBB) at Kepahiang District Health Office. Methods: The research utilized a descriptive qualitative method, analyzing data with an Excel coding system and categorizing them into themes and sub-themes. Purposive sampling was used to select 18 participants for direct, in-depth interviews. Results: complementary therapy practice received a positive response from the community. In addition. On the other hand, all officers did not know about the licensing policy for complementary therapy practices. Conclusion: all informant has had a positive experience; however, they have less knowledge about the policy of implementing complementary therapies